E-Book Interaktif “Pesona” sebagai Media Pembelajaran PAI Inovatif untuk Siswa Sekolah Dasar - Aliya Zahra; Ghina Assaoki; Finka Azrul Fauziyyah; Ani Nur Aeni (Ta’dib : Jurnal Pendidikan Islam, 2025)
This research aims to develop an interactive e-book called “Pesona” (The Journey of the First Prophet Adam) as a learning medium for Islamic Religious Education (IS) on the story of Prophet Adam for second-grade elementary school students. The method used was Design and Development Research, which involved analysis, design, development, and evaluation. Validation results by material and media experts indicated that the e-book was highly valid in terms of both content and presentation. Classroom trials demonstrated that the use of the "Pesona" e-book increased students' understanding and interest in the material. Its attractive visual design, interactive features, and curriculum alignment make this e-book an innovative and effective learning medium for Islamic Religious Education learning.